Mitigation of gaseous mercury emissions from waste-to-energy facilities: Homogeneous and heterogeneous Hg-oxidation pathways in presence of fly ashes - Rumayor, M; Svoboda, K; Švehla, J; Pohořelý, M; Šyc, M (Journal of environmental management, 2018)
This study describes the main mechanisms that take part in the mercury homogeneous oxidation pathway in presence of some of the main reactive compounds formed during waste incineration processes (O2, HCl, SO2 and NO). Series of model, synthetic dry flue gases were used to elucidate the effects of HCl, SO2, NO and their proportions in the gas on mercury behaviour. Three samples of fly ash collected from a MSWI facility were characterized and evaluated both for Hg heterogeneous oxidation and Hg removal in a laboratory scale device. The results obtained in this study showed that homogeneous mercury oxidation in the models MSWI and coal combustion flue gas atmospheres was 52 ± 5% and 25%, respectively. SO2, NO and HCl have a synergetic effect in Hg oxidation in presence of oxygen, but the main differences found are mainly caused by the strong influence of HCl and the likely inhibitory oxidation effects of SO2. Surface area together with carbon and chloride content of the fly ashes were correlated with their capacity for Hg-heterogeneous oxidation and adsorption. The sample of fly ash with relatively high content of unburnt carbon and chlorine, and with BET surface (2.42 m2/g) was able to remove up to 100% of Hg0 (g) during 300 min. The results obtained in this study provide a complete overview of the behaviour of mercury during MSWI processes and may help to clarify the fate/behaviour of mercury in a filter (e.g. electrostatic precipitator) providing a deeper knowledge about the impacts of fly ash properties on mercury fate in waste incineration.
Keywords: Incineration; rtuť; Coal Ash; spalování odpadů; oxidace-redukce; Coal; Gases; Mercury; Oxidation; látky znečišťující vzduch; uhlí; plyny; Air Pollutants; Oxidation-Reduction; popel uhelný; Fly-ash; Waste to energy; Capture